PEMBINAAN PRESTASI SEKOLAH SEPAK BOLA TERANG BANGSA DI KOTA SEMARANG TAHUN 2020 (Universitas Negeri Semarang, 2020)
SSB Terang Bangsa is SSB in Semarang City which was established on October 5, 2009. The formation of SSB Terang Bangsa is based on the vision and mission aimed at fostering athletes both in football and character building towards the professional level. SSB Terang Bangsa has had good achievements by producing athletes who are able to play in the Indonesian League team and the Indonesian national team. The research objective was to determine the implementation of the Terang Bangsa Football School achievement coaching. This research is a qualitative descriptive research. The research location was conducted at SSB Terang Bangsa. Collecting data using observation, interview, and documentation methods. The subjects of this study were athletes, coaches, and administrators. Data analysis techniques using data triangulation techniques. Data analysis with data reduction, data presentation, and drawing conclusions. The results showed that, 1) the development of the achievements of the Terang Bangsa Football School (SSB) was good. Pemassalan is done by interacting directly. Nurseries are carried out in stages according to age groups. The achievements that have been obtained are quite good. 2) Human Resources at SSB Terang Bangsa are good. Athletes who have passion and discipline in training. Competent trainers with C-UEFA and National D certificates. Administrators work with their respective duties. 3) The training program at SSB Terang Bangsa uses a Dutch soccer curriculum that has been adjusted to the conditions of Indonesian football and includes technical, tactical, mental and physical training. 4) The SSB Terang Bangsa organization is good with a clear organizational structure and functions. 5) Facilities and infrastructure at SSB Terang Bangsa are of good quality and adequate completeness. 6) Funding at SSB Terang Bangsa is obtained from athlete contributions and assistance from the foundation. The conclusion of this research is that the implementation of the National Light Football School (SSB) achievement coaching is quite good, this can be seen from the aspects of development, human resources, training programs, organization, facilities and infrastructure, funding. Suggestions recommended for SSB are, 1) Development of achievements at SSB Terang Bangsa is carried out continuously & continuously. 2) Maintaining the quality of human resources both athletes, coaches, administrators. 3) Collaborating with various parties to support the improvement of achievement coaching at SSB Terang Bangsa Semarang.